2016
DOI: 10.1002/hbm.23446
|View full text |Cite
|
Sign up to set email alerts
|

A somatosensory‐to‐motor cascade of cortical areas engaged in perceptual decision making during tactile pattern discrimination

Abstract: The processes underlying perceptual decision making are diverse and typically engage a distributed network of brain areas. It is a particular challenge to establish a sensory-to-motor functional hierarchy in such networks. This is because single-cell recordings mainly study the nodes of decision networks in isolation but seldom simultaneously. Moreover, imaging methods, which allow simultaneously accessing information from overall networks, typically suffer from either the temporal or the spatial resolution ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 21 publications
(44 reference statements)
0
10
0
Order By: Relevance
“…Using a novel parcellation scheme (Korhonen et al, 2014 ), combined with the novel edge-bundling approach (Wang et al, 2018 ), we also identified the network structures of these networks. Delta/theta-band synchronization connected the contralateral SI with ipsilateral SI and SII bilaterally and thereby the brain regions underlying the processing of somatosensory information in monkeys (Haegens et al, 2014 ; Tauste Campo et al, 2015 ) and humans (Hegner et al, 2016 ; Hirvonen & Palva, 2016 ; Jones et al, 2007 ; Jones et al, 2009 ; Li Hegner et al, 2015 ; Papadelis et al, 2016 ). This connectivity pattern positions delta/theta-band synchronization to directly support the processing of somatosensory information.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using a novel parcellation scheme (Korhonen et al, 2014 ), combined with the novel edge-bundling approach (Wang et al, 2018 ), we also identified the network structures of these networks. Delta/theta-band synchronization connected the contralateral SI with ipsilateral SI and SII bilaterally and thereby the brain regions underlying the processing of somatosensory information in monkeys (Haegens et al, 2014 ; Tauste Campo et al, 2015 ) and humans (Hegner et al, 2016 ; Hirvonen & Palva, 2016 ; Jones et al, 2007 ; Jones et al, 2009 ; Li Hegner et al, 2015 ; Papadelis et al, 2016 ). This connectivity pattern positions delta/theta-band synchronization to directly support the processing of somatosensory information.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, fMRI BOLD signal fluctuations in attentional but not in sensory system are also correlated with perceptual performance in a threshold-stimulus detection task like ours (Sadaghiani et al, 2009 ). As PFC and PPC coordinate both perceptual decisions (Donner et al, 2009b ; Goard et al, 2016 ; Hegner et al, 2016 ; Kaplan et al, 2017 ; Siegel et al, 2015 ; Tosoni et al, 2008 ) and conscious perception (Dehaene & Changeux, 2011 ; Gaillard et al, 2009 ; Hirvonen & Palva, 2016 ; Li Hegner et al, 2015 ; Salti et al, 2015 ), we speculate that gamma-band synchronization during the later time windows, however, could underlie conscious perceptual decisions of the weak somatosensory stimuli. The role of gamma-band synchronization in coordinating perceptual decisions was also supported by the distinct temporal profiles of synchronization for fast and slow actions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the neural level, functional magnetic resonance imaging (fMRI) studies show that physical tactile sensations (e.g., vibrations on stationary fingertip) activate a network of brain regions, particularly primary (SI) and secondary (SII) somatosensory cortices ( Christova et al, 2013 ; Chung et al, 2013 ; Kim et al, 2016 ; Simoes-Franklin et al, 2011 ). Other touch-related regions include the insular, cingulate, temporal and parietal regions ( Hegner et al, 2010 , 2017 ; Wei and Bao, 2013 ; Kim et al, 2019 ). Some of these regions show a dependency on the frequency of vibrotactile stimulation ( Harrington and Downs, 2001 ; Hegner et al, 2007 ; Soros et al, 2007 ; Burton et al, 2004 , 2008 , 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Perceptual decision-making is shaped by both afferent feedforward (somatosensory) and cortical feedback mechanisms (Allen et al, 2015; Auksztulewicz et al, 2012; Hegner et al, 2017; Langner et al, 2011). The hierarchical organisation of the brain is such that low-level sensory processing can be dynamically influenced, via feedback mechanisms, by higher-level knowledge (de Lange et al, 2018).…”
Section: Introductionmentioning
confidence: 99%